A rapid, non-invasive and non-destructive method for studying swelling behavior and microstructure variations of hydrogels. (20th October 2016) - Li, Yaqiong; Li, Xiunan; Chen, Chao; Zhao, Dawei; Su, Zhiguo; Ma, Guanghui; Yu, Rong
Highlights: Internal and external water of hydrogels was distinguished by low-field NMR. Swelling ratio was easily determined based on transverse relaxation time ( T2 ). pH responsive swelling behavior was monitored in situ through measuring T2 . Microstructure changes of hydrogels during swelling were analyzed by T2 . Abstract: A new method for studying swelling behavior of hydrogels was developed based on low field NMR (LF-NMR). This method is established on these facts: firstly, internal water (water trapped in hydrogel) and external water (water outside of hydrogel) correspond to different components of transverse relaxation time ( T2 ); secondly, T2 component amplitude is proportional to relative water content; and finally, T2 value is closely related to mesh size of hydrogel network, the main effect being due to the overall concentration (degree of swelling). This method was successfully applied to swelling ratio determination of chitosan/glutaraldehyde (CS/GA) hydrogels in situ, and the results had better accuracy and repeatability compared with that of weighing method. Furthermore, swelling kinetics at different pH and microstructure of CS/GA hydrogels was well elucidated based on T2 . It is clearly showed that LF-NMR provides a powerful tool for probing processes related to water transport and microstructure variation of hydrogels.